Streptococcus salivarius K12 inhibits Candida albicans aggregation, biofilm formation and dimorphism. Issue 7 (9th August 2021) - Mokhtar, Munirah; Rismayuddin, Nurul Alia Risma; Mat Yassim, Aini Syahida; Ahmad, Hasna; Abdul Wahab, Ridhwan; Dashper, Stuart; Arzmi, Mohd Hafiz
Abstract: Candida albicans causes candidiasis, particularly in immunocompromised patients. Streptococcus salivarius K12 (K12) is a probiotic isolated from a healthy oral cavity. The study aimed to determine the effect of K12 on C. albicans aggregation, biofilm formation and dimorphism. C. albicans ATCC MYA-4901, acquired immunodeficiency syndrome (AIDS) isolate (ALC2), and oral cancer isolate (ALC3) and K12 were used in the study. All C. albicans strains and K12 were grown in yeast peptone dextrose agar and brain heart infusion agar, respectively, prior to aggregation, biofilm and dimorphism assays. Auto-aggregation of C. albicans MYA-4901 and ALC2 was categorised as high, while the co-aggregation of the strains was low in the presence of K12. C. albicans total cell count decreased significantly when co-cultured with K12 compared with monocultured C. albicans biofilm ( p <  0.05). Inhibition of yeast-to-hyphae transition was also observed when co-cultured with K12. In conclusion, K12 inhibits C. albicans aggregation, biofilm formation and dimorphism.